2020
DOI: 10.1148/rg.2020190077
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Gamers: Integrating Alternative Input Devices and AutoHotkey Scripts to Simplify Repetitive Tasks and Improve Workflow

Abstract: Radiologists rely heavily on the digital radiology workstation. They spend most of their time interacting with software applications that use multiple input devices, including mice, keyboards, and microphones. The efficiency of this relationship depends on the interface of the different software applications, their interoperability, and input device effectiveness. Because of the repetition of a radiologic workflow, even small inefficiencies can accumulate into significant losses of time and productivity and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 30 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Speech-to-text tools, commonly used in these fields, possibly alleviate some of the perceived administrative burden 3031. Previous research has suggested that text prediction,32 alternative input devices such as specialised keyboards,33 and improvements to the user friendliness of the electronic health record system, as solutions to the problem of administration 3435. Perhaps most importantly, many administrative tasks are thought of as superfluous and can be withdrawn without any impact on the quality of care 36.…”
Section: Discussionmentioning
confidence: 99%
“…Speech-to-text tools, commonly used in these fields, possibly alleviate some of the perceived administrative burden 3031. Previous research has suggested that text prediction,32 alternative input devices such as specialised keyboards,33 and improvements to the user friendliness of the electronic health record system, as solutions to the problem of administration 3435. Perhaps most importantly, many administrative tasks are thought of as superfluous and can be withdrawn without any impact on the quality of care 36.…”
Section: Discussionmentioning
confidence: 99%